Valuing humans over animals: gender differences in meat-eating behavior and the role of the Dark Triad - Mertens, Alica; Krause, Mischa von; Meyerhöfer, Sebastian; Aziz, Céline; Baumann, Felicitas; Denk, Alexandra; Heitz, Theresia; Maute, Johanna (Appetite, 2020)
Empirical findings demonstrate gender differences in attitudes toward meat consumption and actual meat-eating behavior. Furthermore, several studies have found that men score higher on all three Dark Triad personality dimensions (Machiavellianism, narcissism, and psychopathy). In this study, we investigated whether these personality differences mediate the association between gender and meat-eating justification, which in turn was expected to predict meat consumption. Two-hundred-fifty-seven participants took part in the study. We replicated the finding that men score higher on direct justification strategies with respect to meat consumption and report less often that they are vegetarians or vegans. Moreover, and most importantly, gender differences in Machiavellianism (but not in the other Dark Triad traits) significantly mediated these gender differences in meat-eating justification strategies, which in turn predicted meat consumption. These findings support the idea that Machiavellianism is partly able to explain gender differences in meat-eating justification, which is associated with higher meat consumption.
Available online 15 November 2019
Gesehen am 03.06.2020